Perbedaan Berat Cacing African NightCrawler (Eudrilus Eugeniae) Terhadap Kualitas Vermikompos Feses Sapi - Zafira, Windi; Syarifuddin, Hutwan; Novianti, Sri (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aimed to evaluate the effect of different weights of African Night Crawler (Eudrilus eugeniae) on the quality of vermicompost from cow manure. The research was conducted at the Livestock and Forage Cultivation Laboratory, Faculty of Animal Science, University of Jambi, for 30 days. An experimental method using a Completely Randomized Design (CRD) with four treatments and five replications was applied. Treatments were V1 = 20 g worms + 200 g cow manure, V2 = 40 g worms + 200 g cow manure, V3 = 60 g worms + 200 g cow manure, and V4 = 80 g worms + 200 g cow manure. Observed parameters included organic carbon (C), nitrogen (N), phosphorus (P), potassium (K), C/N ratio, and vermicompost pH. Data were analyzed using ANOVA and Duncan’s multiple range test. Results showed that worm weight significantly affected C, N, P, and K contents (P<0.05), but had no significant effect on pH (P>0.05). The highest C and N contents were found in V1 (4.61% and 0.279%, respectively), phosphorus was highest in V4 (2.33 mg/100 g), and potassium was highest in V3 (0.93 mg/100 g). The C/N ratio ranged from 12.19 to 16.50, with the lowest in V2, while pH ranged from 5.9 to 6.9, close to neutral. In conclusion, increasing Eudrilus eugeniae density accelerates cow manure decomposition, reducing carbon and C/N ratio while increasing macronutrients (P and K). Vermicompost from V2 achieved the lowest C/N ratio (12.19), indicating optimal maturity and balanced nutrient content.